Current-Driven Domain Wall Motion in a Planar Nanowire with a Square Hole - Escrig-Murua, J; Tejo-Lazo, F; Vidal-Silva, N (Elsevier B.V., 2019)
The current-driven domain wall motion in a planar nanowire with a square hole located at its center is studied by micromagnetic simulations. We show the existence of four regimes that depend both on the geometrical parameters of the hole and the nanowire, as well as on the applied current density. These regimes determine a pinning-depinning pattern characterized by: i) the domain wall remains pinned in its initial position; ii) the domain wall is released from its initial position and reaches the square hole, remaining pinned in that position; iii) the domain wall reaches the hole and passes it without major obstacles, reaching the other end of the wire; iv) the domain wall reaches the hole and suffers a series of complex transformations that annihilate it, giving rise to the nucleation of a new domain wall, which is what reaches the other end of the wire. Our finding could be of practical use in the engineering of logic devices based on the movement of domain walls. © 2019 Elsevier B.V.